Economic evaluations in fracture research an introduction with examples of foot fractures. Issue 3 (March 2022) - van den Boom, NAC; van den Hurk, AA; Kalmet, PHS; Poeze, M; Evers, SMAA
Highlights: "The incidence of traumatic foot fractures is increasing. Next to this, the need for economic evaluation studies is growing fast.". "The aim of this review is to introduce economic evaluation to medical professionals using traumatic foot fractures as a focal point.". "Understanding the mechanisms of economic evaluation is essential for medical professionals when using it in developing clinical guidelines.". "Literature about economic evaluation studies in foot fracture research is lacking in numbers and in quality, more good literature is necessary.". "When using economic evaluations, one should be aware of the perspective used, as the results of the study will differ depending on this perspective.". Abstract: Introduction: The incidence of foot fractures is increasing. These types of fractures represent the most expensive group of diagnoses in the emergency department. Next to this, the need for economic evaluation studies is growing fast. The aim of this article is to provide healthcare professionals with an introduction to economic evaluation studies in the field of foot fractures. Types of economic evaluation studies: Four types of economic evaluation studies exist: cost-minimization analysis (CMA), cost-benefit analysis (CBA), cost-effectiveness analysis (CEA), and cost-utility analysis (CUA). An economic evaluation study can be either trial- or model-based. Cost Assessment: When assessing costs in an economic evaluation study, three steps need to be made: identification of costs, measurement of costs, and valuation of costs. Perspective of analysis: Two main perspectives exist in economic evaluation studies. When using a healthcare perspective, only the potential costs and benefits of an intervention for the healthcare sector are included. The societal perspective includes all potential costs, including societal costs. Synthesis of costs and effects and uncertainty analysis: The level of cost-effectiveness can be objectively expressed using the incremental cost-effectiveness ratio (ICER). This measure can be plotted in a cost-effectiveness plane and can be compared with existing regional ceiling ratios. Conclusion: Although this article is not a guideline for economic evaluations, we do want to present five tips to consider when performing an economic evaluation. Firstly, when measuring resource use, consult the Database of Instruments for Resource Use Measurements (DIRUM) to find an appropriate instrument. Secondly, when measuring utility values, use the EuroQol questionnaire if possible. Thirdly, when setting up an economic evaluation study, consult the International Society for Pharmacoeconomics and Outcomes Research (ISPOR) database for the appropriate pharmacoeconomic guidelines. Fourthly, consult international guidelines to decide which study design is most appropriate. Finally, when performing an economic evaluation, consult a heath technology assessment (HTA) specialist from the start to ensure methodological quality.